2008
DOI: 10.1002/mame.200800139
|View full text |Cite
|
Sign up to set email alerts
|

Polymer/Clay Nanocomposites: Influence of Ionic Strength on the Structure and Adhesion Characteristics in Multilayered Films

Abstract: The aim of the present contribution is to understand how ionic strength, brought by the addition of salt to laponite/PEO nanocomposite dispersions, influences the texture and adhesion characteristics at nano‐ and microscales in multilayered nanocomposite films prepared from such dispersions. At the nano‐scale, SAXS and XRD measurements indicated that the clay platelets orient parallel to the film plane and that the polymer chains intercalate the clay platelets regardless of salt addition. A gradual transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Like most references, 6,[10][11]22 in this study, a water-soluble PVA was chosen as an organic binder to fabricate clay-polymer composites in the form of a membrane in which clay sheets are in the form of stacked bricks. There are three kinds of water-based polymer systems: water-soluble, waterborne, and water-dispersed.…”
Section: Fabrication Of Clay-pva Nanocomposite Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like most references, 6,[10][11]22 in this study, a water-soluble PVA was chosen as an organic binder to fabricate clay-polymer composites in the form of a membrane in which clay sheets are in the form of stacked bricks. There are three kinds of water-based polymer systems: water-soluble, waterborne, and water-dispersed.…”
Section: Fabrication Of Clay-pva Nanocomposite Filmsmentioning
confidence: 99%
“…6 Considering Sample C as an example, the photograph in Fig. This phase change results from the fact that while partial PVA repeating units connect with clay sheets via a hydrogen bond (O-H/O-), the connection points become hydrophobic because of the lack of active sites with water molecules.…”
Section: Fabrication Of Clay-pva Nanocomposite Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within such systems, the clay stacks are poorly wrapped in polymer and agglomerate to form larger clay‐rich clusters. The excess polymer forms a mesh that covers these large agglomerates, generating a polymer‐rich area outside the clusters 26…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in PEO‐montmorillonite nanocomposites the heterogeneous nucleation of PEO competes with the PEO coordination to sodium ions, which inhibit PEO crystallinity 23–25. Recently, we have shown, via AFM studies, that when no electrolyte salt is added to the PEO/clay system the polymer/clay interactions in solution are diminished and the final structure of the resultant multilayered film is a combination of polymer‐rich and clay‐rich domains 26. Within such systems, the clay stacks are poorly wrapped in polymer and agglomerate to form larger clay‐rich clusters.…”
Section: Introductionmentioning
confidence: 99%